Virtual Learning - Cvetkovic, Dragan (IntechOpen, 2016)
The first chapter provides an overview of the popular systems for distance learning. In the second chapter, a review of all major social and economic activities in order to improve the system of virtual learning is given. The third chapter deals with the influence of technology in the management of educational institutions. The fourth chapter provides an overview of the graphic communication. The fifth chapter confirms that quality assurance remains an integral and indispensable part of the process of virtual learning. The sixth and seventh chapters are dedicated to health and mutual communication about health problems and causes. The eighth and ninth chapters are dedicated to massive open online courses (MOOC). The tenth chapter refers to the widespread use of virtual reality in industrial environments.